2013
DOI: 10.5772/57144
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Synthesis of the Bioconjugate Folic Acid-Gold Nanoparticles

Abstract: In this paper we present a rapid and simple onepot method to obtain gold nanoparticles functionalized with folic acid using a photochemistry method. The bioconjugate folic acid-gold nanoparticle was generated in one step using a photo-reduction method, mixing hydrogen tetrachloroaurate with folic acid in different ratios and varying the illumination time of a mercury lamp (λ= 255 nm). Scanning electron microscopy showed a particle size of around 40-50nm and dynamic light scattering exhibited that the zeta pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…The TEM result of AuNPs was shown in Figure 2, which indicated that the AuNPs had a uniform size; the diameter was about 16 nm, as well as the particle shape was spherical; and the dispersion was even [22].…”
Section: Resultsmentioning
confidence: 99%
“…The TEM result of AuNPs was shown in Figure 2, which indicated that the AuNPs had a uniform size; the diameter was about 16 nm, as well as the particle shape was spherical; and the dispersion was even [22].…”
Section: Resultsmentioning
confidence: 99%
“…FA was obtained from Sigma-Aldrich Corp. All chemicals used in this study were of analytical grade. FA solutions were prepared as described by Castillo et al [17]. FA molecules were dissolved in water with an addition of 50 µL of NaOH (1 M), due to the poor solubility of FA.…”
Section: Preparation Of Fa Solutionsmentioning
confidence: 99%
“…Four P6CA/HAuCl 4 .3H 2 O molar ratios (0.44/1, 0.5/1, 0.56/1, and 0.62/1) were used to evaluate the effect of AuNP growth in the synthesis of P6CA-AuNP. These molar ratios were selected based on previous FA-AuNP synthesis works [18,25]. When UV-Vis spectra of products were analyzed, the characteristic SPA band of spherical AuNPs could be observed around 530 nm for 0.56/1 ratio (see Fig.…”
Section: Resultsmentioning
confidence: 99%